2000
DOI: 10.1038/sj.onc.1203584
|View full text |Cite
|
Sign up to set email alerts
|

Altered natural killer cell differentiation in CD34+ progenitors from Chronic Myeloid Leukemia patients

Abstract: IL-15 and SCF fail to induce NK di erentiation and proliferation of CD34 + hematopoietic progenitors from chronic myeloid leukemia patients in contrast to normal stem cells although, both normal and leukemic CD34 + cells display comparable expression of c-kit or IL-15 receptor subunits. Interestingly, confocal microscopy analysis revealed that leukemic and most normal CD34 + cells produce and secrete IL-15, as shown by its tra cking through the Golgi apparatus and early endosomes. However, only leukemic progen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
24
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 32 publications
3
24
0
Order By: Relevance
“…3, C and D). This observation suggests that translation or intracellular trafficking of IL-15 in HGF is regulated, which is in agreement with recent reports showing that IL-15 is constitutively expressed on fibroblasts from human spleen and skin and also on human monocytes and leukemic progenitors without any IL-15 secretion (22)(23)(24)(25)(26). Considering these findings, it is conceivable that HGF express endogenous IL-15 as the membranebound IL-15, which is the transcript encoding 48 aa-IL-15.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…3, C and D). This observation suggests that translation or intracellular trafficking of IL-15 in HGF is regulated, which is in agreement with recent reports showing that IL-15 is constitutively expressed on fibroblasts from human spleen and skin and also on human monocytes and leukemic progenitors without any IL-15 secretion (22)(23)(24)(25)(26). Considering these findings, it is conceivable that HGF express endogenous IL-15 as the membranebound IL-15, which is the transcript encoding 48 aa-IL-15.…”
Section: Discussionsupporting
confidence: 79%
“…Another neutralizing anti-IL-15 mAb showed the same results and cross-linking of IL-15/IL-2R␤/␥ c or IL-2R␤/␥ c by addition of mAbs to the molecules followed by antimouse IgG did not alter the expression of IL-2R␤ and ␥ c (data not shown), indicating that neutralizing anti-IL-15 mAb inhibited binding of IL-15 to IL-2R␤ and ␥ c on the cell surface, and excludes the possibility that the anti-IL-15 induced inhibitory effect by cross-linking of IL-15/IL-2R␤/␥ c . Recent reports showed that neutralizing the anti-IL-15 mAb inhibited ␥ c expression in CD34 ϩ hemopoietic progenitors (26,30), but had no clear effect on IL-2R␤. Another report showed that the formation of the IL-15/IL-15R␣ complex on lymphoid cell surfaces induced a trans-endosomal recycling of IL-15 leading to the persistence of surface-bound IL-15 (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, blood-derived cells, including monocytes, monoblastoid cells, and leukemic progenitors, have been reported to constitutively express membrane-associated IL-15 without any IL-15 secretion (27)(28)(29). This membrane form has been proposed to be the bioactive form of IL-15 (27) and the result of IL-15 mobilization from intracellular stores to the membrane (30).…”
Section: Discussionmentioning
confidence: 99%
“…18 The possibility to differentiate NK cells in vitro has raised the question of NK-cell differentiation in patients with myeloid disorders. We showed that the in vitro development of NK cells from CML progenitors was altered, 19 suggesting that such alterations may lead to the decreased function of peripheral NK cells described in CML patients. We also found a severe alteration in NK-cell differentiation from CD34 þ cells derived from MDS patients.…”
mentioning
confidence: 94%